Eleven sectors’ reaction to the political event 2023: evidence from Indonesia Stock Exchange - Rochimah, Ainun; Yuliana, Indah (Journal of Accounting and Investment, 2024)
Research aims: This study analyzes the differences in market reaction towards eleven sectors in the Indonesia Stock Exchange (IDX) during the political event, i.e., the announcement of the Indonesian presidential and vice-presidential nominees in 2023.Design/Methodology/Approach: This study applied the event study method with indicators of abnormal return, trading volume activity, security return variability, and bid-ask spread. The hypothesis test was a non-parametric test by Wilcoxon Signed Rank Test with a window period of seven days of observation (-3, 0, +3).Research findings: The Wilcoxon Signed Rank Test results revealed a mixed reaction by eleven sectors in IDX to this political event, in which there was a difference and no difference in the reactions.Theoretical contribution/Originality: This study contributes to providing insight into the reaction of eleven different sectors in the IDX to the different announcements of the Indonesian presidential and vice-presidential nominees in 2023. Previous research usually focused on stock indices or only testing one particular sector. Hence, this study investigated eleven sectors in the capital market to compare the different reactions and to expand the results.Practitioner/Policy implication: Research on capital market reactions to political events provides important information for investors to make investment decisions based on investor sentiment that assesses the electability of prospective heads of state to advance the Indonesian economy.Research limitation/Implication: The scope of this study is the announcement of the Indonesian presidential and vice-presidential nominees in 2023; future researchers can continue research on capital market reactions to the Indonesian presidential election 2024 events and add relevant variables, such as foreign sales and foreign buys.